2017
DOI: 10.1038/s41598-017-13624-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of tillage and residue on spring maize yield through regulating root-shoot ratio in Northeast China

Abstract: In recent years, yield instability of spring maize becomes increasingly pronounced under the traditional cropping system. In 2014 and 2015, short-term effects of tillage (plow-till, rotary-till and no-till) and residue (removal and incorporation) on soil properties, maize growth and yield were investigated in a brown soil region. Our results indicated that short-term reduced tillage (rotary-till and no-till) and residue incorporation promoted soil properties and maize growth. Compared with plow-till, rotary-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Since lower values of CI are associated with faster rates of decomposition and nutrient turnover, our results suggest that changes in nematode communities under reduced tillage may contribute to the increased capability of the system to retain nutrients and store carbon (Griffiths et al, ). The higher relative and absolute abundance of herbivorous nematodes in reduced tillage compared to conventional tillage is in line with previous studies (Brmež et al, ; Freckman & Ettema, ; Fu et al, ; Treonis et al, , ), and can be explained by a higher incidence of rootsin the field, stimulating this nematode group (Minton, ; You et al, ) Our results indicate a possible trade‐off in reduced tillage systems in terms of soil processes, and that in these types of systems care must be taken regarding the assessment and control of herbivorous nematodes. However, the higher alpha diversity, MI and SI found in reduced tillage could indicate that the activity of herbivorous populations might be controlled by a more stable and structured food web.…”
Section: Discussionsupporting
confidence: 90%
“…Since lower values of CI are associated with faster rates of decomposition and nutrient turnover, our results suggest that changes in nematode communities under reduced tillage may contribute to the increased capability of the system to retain nutrients and store carbon (Griffiths et al, ). The higher relative and absolute abundance of herbivorous nematodes in reduced tillage compared to conventional tillage is in line with previous studies (Brmež et al, ; Freckman & Ettema, ; Fu et al, ; Treonis et al, , ), and can be explained by a higher incidence of rootsin the field, stimulating this nematode group (Minton, ; You et al, ) Our results indicate a possible trade‐off in reduced tillage systems in terms of soil processes, and that in these types of systems care must be taken regarding the assessment and control of herbivorous nematodes. However, the higher alpha diversity, MI and SI found in reduced tillage could indicate that the activity of herbivorous populations might be controlled by a more stable and structured food web.…”
Section: Discussionsupporting
confidence: 90%
“…Mangalassery et al (2014) reported an increase in D b under NT in a 9-yr experiment in East Midlands of the U.K. Heard et al (1988), however, reported lower D b in NT systems than in plowed plots at 20-to 30-cm soil depths. In a 2-yr study, You et al (2017) reported no significant effect of increased D b and compaction on spring corn yield in China. In the Argentine Pampas, in general, increases in D b under NT were negligible, averaging about 4% (Alvarez and Steinbach, 2009).…”
Section: Impact Of Soil Bulk Density Changesmentioning
confidence: 95%
“…Canopy is the direct foundation of crop yield, and shoot is clearly the highest priority from an economic view point. Obviously, crops that can access the required soil resources at a lower cost are more productive (Lynch & Ho, ; Lynch et al., ; You et al., ). There were no significant differences between CK and FM in terms of root biomass at the V3 stage (Figure 4a; Table ), but the RL of CK was dramatically increased (Figure 4c; Table ); CK intended to distribute 4–9% more root biomass in deeper soil layer (10–30 cm underground; Table ).…”
Section: Discussionmentioning
confidence: 99%